INFLUENCE OF AUDITOR TURNOVER, KAP REPUTATION, AUDIT OPINION ON AUDIT DELAY WITH AUDIT LAG AS INTERVENING VARIABLE (International Conference on Social and Islamic Studies, 2021)
Financial reports are a tool that is used as a measuring tool that is used as a basis for a company's decision making. Quality and timeliness in financial reports can be used as a reference and investor confidence if the company can provide accurate, clear, and precise information and information that can be compared with other indicators. The purpose of this study is to find out the effect of auditor turnover, KAP reputation, audit opinion on audit delay with audit lag as an intervening variable (case studies on consumer goods companies registered with IDX period 2018-2019). This study used secondary data in the form of annual company reports and independent audit reports with a sample of 43 companies from the population of consumer goods companies registered with the IDX in 2018-2019. Data collection techniques use library study methods (data documentation) from secondary data sources. Data analysis techniques use multiple linear regression analysis and SPSS 25.0 software. The results showed that the auditor turnover, KAP reputation, and audit opinion did not affect audit delay, while audit lag could not mediate audit opinion against audit delay. The advice for future research is to be able to add other research variables that are factors that influence audit delay, as well as to research audit lag as a mediation variable.